2016
DOI: 10.1111/conl.12310
|View full text |Cite
|
Sign up to set email alerts
|

Are Brazil's Deforesters Avoiding Detection?

Abstract: Rates of deforestation reported by Brazil’s official deforestation monitoring system have declined dramatically in the Brazilian Amazon. Much of Brazil’s success in its fight against deforestation has been credited to a series of policy changes put into place between 2004 and 2008. In this research, we posit that one of these policies, the decision to use the country’s official system for monitoring forest loss in the Amazon as a policing tool, has incentivized landowners to deforest in ways and places that ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 26 publications
(46 reference statements)
3
48
0
2
Order By: Relevance
“…The results of this study directly inform decision makers regarding the contributions from forests towards reducing net emissions of greenhouses gases (Bull et al 2013, Food and Agriculture Organization of the United Nations 2015), progress towards the zero net deforestation commitments (WWF 2008, GCP 2015, and potential to national commitments to restore 12 Mha by 2030 (MMA 2018). Without SV, national deforestation and greenhouse emissions inventories are incomplete (Pereira and Vieira 2001, Zarin et al 2001, Richards et al 2017.…”
Section: Recommendations For Public Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study directly inform decision makers regarding the contributions from forests towards reducing net emissions of greenhouses gases (Bull et al 2013, Food and Agriculture Organization of the United Nations 2015), progress towards the zero net deforestation commitments (WWF 2008, GCP 2015, and potential to national commitments to restore 12 Mha by 2030 (MMA 2018). Without SV, national deforestation and greenhouse emissions inventories are incomplete (Pereira and Vieira 2001, Zarin et al 2001, Richards et al 2017.…”
Section: Recommendations For Public Policiesmentioning
confidence: 99%
“…Other systems such as the Global Forest Change (GFC) (Hansen et al 2013) and TerraClass project (Terra-Class 2014) provide information on SV cover, but do not track SV age or separate the contribution from SV to tree cover loss (see supplementary section 3, available online at stacks.iop.org/ERL/15/034057/ mmedia). In summary, data gaps on SV prevent a complete accounting of Amazon deforestation, greenhouse gas emissions, and net carbon uptake by SV (Assunção and Gandour 2017;Richards et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…12,13,14 . Forest area, spatial distribution, temporal dynamics and annual rates of forest loss have been contentious for decades 12,15,16 . Two recent studies 15,17 reported that both the official Brazilian deforestation dataset (PRODES) 18 and Global Forest Watch (GFW) 11 missed relatively large areas of forest loss.…”
Section: Introductionmentioning
confidence: 99%
“…Forest area, spatial distribution, temporal dynamics and annual rates of forest loss have been contentious for decades 12,15,16 . Two recent studies 15,17 reported that both the official Brazilian deforestation dataset (PRODES) 18 and Global Forest Watch (GFW) 11 missed relatively large areas of forest loss. For instance, approximately 9,000 km 2 of forest loss was not reported by the PRODES dataset for 2008-2012 due to the 6.25-ha minimum mapping unit 15 .…”
Section: Introductionmentioning
confidence: 99%
“…While the article provides a useful comparison of PRODES and two other monitoring systems, we strongly disagree with the authors’ suggestion that Brazil's monitoring systems are “antiquated and incomplete” and that they do not provide the basis for “transparently achieving Brazil‘s GHG (greenhouse gases) mitigation commitments” (Richards et al . : 11). Richard's et al .…”
Section: Main Forest Monitoring Systems Developed By the Brazilian Gomentioning
confidence: 97%